2011
DOI: 10.1111/j.1365-2788.2011.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental report of sleep problems in Down syndrome

Abstract: Children with DS are at risk for developing symptoms of sleep disordered breathing, and may have additional sleep problems that are unrelated to sleep disordered breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 23 publications
6
88
0
3
Order By: Relevance
“…6,21,22 The CSHQ yields both a total score and eight subscale scores, reflecting key sleep domains in school-aged children. Here we report parent ratings of sleep-disordered breathing and daytime sleepiness subscales, with higher scores reflecting poorer sleep behaviors.…”
Section: Parent-reported Sleepmentioning
confidence: 99%
“…6,21,22 The CSHQ yields both a total score and eight subscale scores, reflecting key sleep domains in school-aged children. Here we report parent ratings of sleep-disordered breathing and daytime sleepiness subscales, with higher scores reflecting poorer sleep behaviors.…”
Section: Parent-reported Sleepmentioning
confidence: 99%
“…Esta pesquisa foi a primeira a investigar os aspectos do sono e de atenção em escolares com SD e SW e salientou a necessidade de se investir em estudos futuros para melhor contribuições da atenção, do sono e sua influência nesses dois grupos (ASHWORTH et al, 2014). No entanto, observou-se que há caracterísicas comuns aos dois grupos com se sem deficiência, tais como ronco, agitação noturna, irritação, respiração ruidosa, pausas respiratórias, déficit de atenção, instabilidade de humor e dificuldade de socialização, cooperação (MARTINEZ, 1999;GOTTLIEB;CHASE;VEZIN, 2004;VALERA;DEMARCO;ANSELMO-LIMA, 2004;BRESLIN et al, 2011;ASHWORTH, et al, 2013;BUCKHALT, 2013). Observou-se que o exame indicado para avaliar os DRS é a polissonografia (MACEDO; COLOMBINI; PINTO, 2010).…”
Section: Desta Forma O Estudo Que Bonuck Et Al (2011) Realizaram Nunclassified
“…Porém, devido aos elevados custos do exame, muitas pesquisas têm avaliado a qualidade do sono por meio de questionários padronizados do sono. Tal situação tem sido recorrente no diagnóstico dos escolares com e sem deficiência (MAAS et al, 2009;BRESLIN, 2011). Outro instrumento que os pesquisadores dos distúrbios do sono têm utilizado para avaliação das crianças e adolescentes com deficiência é a actigrafia.…”
Section: Desta Forma O Estudo Que Bonuck Et Al (2011) Realizaram Nunclassified
“…Bedtime resistance, sleep anxiety, night waking, parasomnias and daytime sleepiness have all been reported commonly in children with DS [11,[13][14][15]24]. Carter et al [11] used the Child Sleep Habits Questionnaire (CSHQ) and found that parents universally reported sleep problems in school-aged children with DS that persisted into teenage years.…”
Section: Prevalence Of Sleep Disorders In Children With Down Syndromementioning
confidence: 99%
“…Large inter-individual differences are seen within the DS population and numerous factors including genetics, epigenetics, early neural development and the environment are thought to have a role in how the DS phenotype expresses itself in each individual [7]. Variation in sleep patterns and sleep disruption, has been highlighted as another potential factor that could contribute to the wide phenotypic differences in DS; individuals with DS often have sleep fragmentation due to common co-existing sleep disorders [8][9][10][11][12][13][14][15]. The degree of sleep difficulties in an individual with DS may be important in determining their predisposition to cognitive decline, by contributing to pathological ageing [16].…”
Section: Introductionmentioning
confidence: 99%